2007
DOI: 10.1177/0306396807077009
|View full text |Cite
|
Sign up to set email alerts
|

From Good Friday to Good Relations: sectarianism, racism and the Northern Ireland state

Abstract: This article addresses the nature of contemporary racism and sectarianism in Northern Ireland in the context of the Good Friday Agreement (GFA) and its outworking. It responds to the increasing dominance of the 'good relations' model for understanding and addressing race and sectarian division in Northern Ireland. It debunks the gathering support for the notion that Northern Ireland is somehow 'post-sectarian' -finding instead a state formation that hides its incapacity to address rising racism and sectarianis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 7 publications
1
50
0
Order By: Relevance
“…Our first research question was whether negative attitudes towards immigrants and ethnic minorities are more prevalent in Northern Ireland than in other regions of the UK, thus justifying to label the region the "race hate capital of the UK" (Lentin and McVeigh 2006;McVeigh and Rolston 2007;Knox 2011). To answer this, we carried out a UK-wide comparison of negative population attitudes towards immigrants, Muslims and Eastern Europeans using the NILT and BSA data.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our first research question was whether negative attitudes towards immigrants and ethnic minorities are more prevalent in Northern Ireland than in other regions of the UK, thus justifying to label the region the "race hate capital of the UK" (Lentin and McVeigh 2006;McVeigh and Rolston 2007;Knox 2011). To answer this, we carried out a UK-wide comparison of negative population attitudes towards immigrants, Muslims and Eastern Europeans using the NILT and BSA data.…”
Section: Resultsmentioning
confidence: 99%
“…In the wake of the Brexit vote in the UK and Donald Trump's presidential campaign in 2016, both of which were to a large extent driven by anti-immigrant sentiment, group threat theory has gained in salience. Empirical cross-national comparisons (McLaren 2003;Schneider 2007;Borgonovi 2012, Doebler 2014 and case studies from the UK (Ford 2008;Cutts, Ford, and Goodwin 2011), the Netherlands (Coenders and Scheepers 2003;Billiet and De Witte 2008;Van Assche et al 2014), Germany (Wagner, Christ, and Pettigrew 2008) and Northern Ireland (Hayes and Dowds 2006;McVeigh and Rolston 2007;McKee 2015) confirmed that lower educational achievement and lower socio-economic status are associated with an increased likelihood of perceiving immigrants and ethnic minorities as a threat. Particularly in the case of Northern Ireland, group threat theory is a plausible candidate for explaining anti-immigrant negativity, since the history of sectarian hostility was theorized by several scholars as based on economic and power struggles between the two (Protestant vs. Catholic) ethnic/religious groups (Brewer 1992;Anderson and Shuttleworth 1998;McVeigh and Rolston 2007;Brewer 2015).…”
Section: Negativity Towards Immigrants and Ethnic Minorities In The Lmentioning
confidence: 89%
See 1 more Smart Citation
“…These internal and external constructions therefore may constitute a significant aspect of their sum total of reality and, accordingly, of their symbiotic interaction with the institutions of society, and those privileged to carry out research on 'them'. It has been argued recently that racism must continuously mutate in order for it to survive (McVeigh & Rolston, 2007). Gilroy (1987, p. 11) echoes this sentiment: 'Racism does not, of course, move tidily and unchanged through time and history.…”
Section: Introductionmentioning
confidence: 99%
“…There, a remarkable persistence and deepening of 'postconflict' sectarian division has been demonstrated (Shirlow and Murtagh, 2006). Yet, with notable exceptions (Anderson and Shuttleworth, 1998;McVeigh and Rolston, 2007;Garvey and Stewart, 2015), previous studies of migration and work also have tended to separate out worker experiences from broader societal relations and structures (e.g. Bell et al, 2004;Jarman, 2004) and underplay the ways in which social context and location are linked to labour market insecurity in shaping precarious employment and living experience (see Vosko, 2006).…”
mentioning
confidence: 99%